Pengaruh Motivasi Kerja Dan Lingkungan Kerja Fisik Terhadap Kinerja Karyawan Pada PD. Erasumpindo Sejati Tigaraksa Kabupaten Tangerang - Abid Hibatullah Ramadhan; Oki Iqbal Khair (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
Abstract. This study aims to determine the effect of work motivation and physical work environment on employee performance at PD. Erasumpindo Sejati. This study uses a quantitative method. The sampling technique is using a saturated sample with a total of 81 respondents. The results of this study indicate that work motivation and physical work environment influence employee performance by obtaining a regression equation Y = 22.277 + 0.451, the correlation coefficient value or the level of relationship between the independent variable and the dependent variable is obtained at 0.67.5, meaning that these three variables have a strong relationship with each other. The coefficient of determination or contribution of the influence of work motivation and physical work environment simultaneously is 67.5% while the remaining 32.5% is influenced by other factors not carried out in this study. The partial hypothesis test (t-test) of work motivation on employee performance shows a calculated t value of 5.275> t table 1.664 or a Sig value of 0.000 <0.05. The partial hypothesis test (t-test) of the physical work environment on employee performance showed a calculated t-value of 4.439 > t-table 1.664, or a sig. 0.000 <0.05. Meanwhile, the simultaneous hypothesis test (F-test) showed a calculated f-value of 18.984 > f-table 3.11, or a sig. 0.000 <0.05. Hypothesis testing indicates a positive and significant influence, both partially and simultaneously, between work motivation and the physical work environment on employee performance at PD. Erasumpindo Sejati Tigaraksa, Tangerang Regency